Absence of a Derogation Clause under the African Charter and the Position of the African Commission - Aboma, Melkamu Tolera (Bahir Dar University Journal of Law, 2022)
A Derogation clause is an important limitation on state’s powerduring a state of emergency when human rights are in a precarioussituation. This article analyses the omission of derogation clause fromthe African Charter. It examines international and regional humanrights instruments, the jurisprudences of human rights monitoringbodies relating to issues of derogation and academic writings. Thefindings of this article show the absence of a derogation clause in theAfrican Charter is a serious flaw that should be corrected.